(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Diabetes mellitus (DM) is the most prevalent metabolic, non-communicable disorder in the world. Diabetic nephropathy(DN) is one of the most serious complications of diabetes leading to end-stage renal failure. Venous impedance index in diabetic nephropathy may predict the early hemodynamic changes in the renal parenchyma of these patients before the clinical onset of nephropathy. Objective: To observe the difference between values of intrarenal venous impedance index measured by duplex color Doppler USG in patients with diabetic nephropathy and in nondiabetic healthy control subjects. Materials and methods: This cross-sectional study was done in the department of Radiology and Imaging, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM). For this purpose, 80 diabetic nephropathy patients were taken as study group and 80 healthy subjects were included as healthy control subjects. Duplex Color Doppler Sonography of intrarenal veins was carried out in both groups to measure the Peak Venous Flow Signal, the Least Venous Flow Signal and Venous Impedance Index. Results: The mean age of the control subjects was 46.93 (± 8.864) years and that of the case patients was 48.39 (±11.994) years. In control group 48 (60%) were male and 32 (40%) were female where as in case group 44 (55%) were male and rest 36 (45%) were female patients. In control subjects the mean value of peak venous flow signals was significantly higher for right kidney but in case group no such difference was observed. The mean venous impedance index of right kidney in control group was 494 ± 0.125 and the mean venous impedance index of right kidney in diabetic nephropathy patients was 2746 ± 0.102. The mean difference of venous impedance index of right kidney in the two groups was statistically highly significant (p<.001). The mean venous impedance index of left kidney in control group was 0.485 ± 0.014 and the mean venous impedance index of left kidney in diabetic nephropathy patients was 0.259 ± 0.101. The mean difference of venous impedance index of left kidney in the two groups was statistically highly significant (p<.001). The mean renal VII of normal controls was 0.4895 (± 0.133) and in DN patients the mean renal VII value was 0.2668 (± 0.101). In reference to VII values in DN patients, it can be suggested that VII would be considered normal if >0.30. Conclusion: It can be concluded that VII remains significantly lower in patients with DN than in controls. The underlying mechanism could be related to interstitial fibrosis in DN kidneys progressively reducing tissue compliance. Lower VII in diabetic nephropathy may predict the early hemodynamic changes in the renal parenchyma of these patients before the clinical onset of nephropathy. BJRI, 2024; VOL. 32(2): 99-106